The Qualitative Study of the Phenomenon of Premarital Sex: Between Expectations and Reality Among Adolescents in Banjarmasin - Esti Yuandari; R. Topan Aditya Rahman; Ika Avrilina Haryono; Nurul Hidayah; Novita Dewi Iswandari; Siti Hateriah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Premarital sex has become an increasingly concerning issue, particularly in the context of social and health aspects. This study to delve deeper into the factors influencing premarital sexual behaviour among adolescents and its impacts on their physical and social health. Methods: This study employ’s a qualitative phenomenological design using a bracketing approach to capture the phenomenon purely and objectively from the informant's perspectives, with sampling conducted through a snowball technique involving four participants aged 15 to 19 years. Results: The results indicated that the flocking phenomenon and an overestimated perception of peers are the main factors driving adolescents to engage in premarital sexual relationships, which they perceive as a demonstration of love towards their partners. Conclusion: This study recommends the need for enhanced education on values, norms, and the preservation of Eastern culture that is comprehensive, along with parental involvement in educating their children to face these challenges more effectively. By understanding this phenomenon, it is hoped that effective solutions can be found to reduce the risks and negative impacts of premarital sex.